PENDIDIKAN ISLAM BERBASIS KEARIFAN LOKAL PADA ANAK USIA DINI DI LINGKUNGAN PESANTREN - Rasidi; Iftitah, Selfi Lailiyatul (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2025)
This study aims to describe the implementation of local wisdom-based Islamic education in early childhood in Islamic boarding schools and analyze its influence on character building in children. The study uses a descriptive qualitative approach and is conducted at the Taman Bunga Pamekasan Islamic boarding school, which has an early childhood education unit. Data were collected through participatory observation, in-depth interviews, and document analysis, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that Islamic education based on local wisdom is implemented through formal classroom learning, children's involvement in pesantren religious activities, and the cultivation of daily behaviors. Pesantren traditions such as tahlilan, marhabanan, kenduri, gotong royong, and respect for teachers serve as effective means to instill religious values, etiquette, solidarity, independence, and social responsibility in children. The exemplary behavior of teachers and pesantren caregivers plays a crucial role in the successful implementation of these values. This study concludes that the Islamic education model based on local wisdom at the Taman Bunga Pamekasan Islamic boarding school not only shapes children with noble character and an understanding of religious teachings but also strengthens their cultural identity. This model can serve as a strategic alternative for the development of character education for young children, particularly in regions with a rich tradition of Islamic-local heritage that remains preserved.